2017
DOI: 10.1038/s41598-017-01849-3
|View full text |Cite|
|
Sign up to set email alerts
|

Solitonic conduction of electrotonic signals in neuronal branchlets with polarized microstructure

Abstract: A model of solitonic conduction in neuronal branchlets with microstructure is presented. The application of cable theory to neurons with microstructure results in a nonlinear cable equation that is solved using a direct method to obtain analytical approximations of traveling wave solutions. It is shown that a linear superposition of two oppositely directed traveling waves demonstrate solitonic interaction: colliding waves can penetrate through each other, and continue fully intact as the exact pulses that ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…The model presented herein constitutes a first attempt at identifying solitons as electrotonic signals propagating in neuronal branchlets with microstructure containing mitochondria. The model differs from that of Poznanski and colleagues [ 22 ] where solitonic conduction of electrotonic potentials was due to charged proteins without mitochondrial membranes.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The model presented herein constitutes a first attempt at identifying solitons as electrotonic signals propagating in neuronal branchlets with microstructure containing mitochondria. The model differs from that of Poznanski and colleagues [ 22 ] where solitonic conduction of electrotonic potentials was due to charged proteins without mitochondrial membranes.…”
Section: Discussionmentioning
confidence: 66%
“…However, the model of Poznanski [ 21 ] did not take into account polarization current due to the dispersion of bound charge held by microstructure. An instance where charge dispersal is not ignored, the voltage created by charge ‘soakage’ due to intracellular capacitive effects has been modeled through voltage-dependent capacitors [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such non-linear filtering operations could be biologically implemented by active dendritic membrane processes that were shown to exist in VS cells 40 and by nonlinear voltage-calcium relationship 41 . In addition, two recent elegant studies have shown that nonlinear phenomena are expected in thin dendrites at the sub-micron regime (<0.5 μm) 42 , 43 . The average diameter of the branchlets in our dataset is 1.02μm (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, excitation waves from propagating graded potentials to action-potential, show an entire range of interactions; from superposition to supra-linear, to sublinear summation (57). Upon interaction, these waves can emerge unaffected (48,49) to being annihilated (58,59). Shock physics as developed for lipid monolayer now provides a general mechanism for such interactions at interfaces.…”
Section: Discussionmentioning
confidence: 99%